The Influence Of Emotional Intelligence On Employee Performance In The Business Sector - Nabila Mukmininah Jibril; Lidya Anastasya; Hadira Thumaninah Jibril (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
: Emotional intelligence (EI) refers to an individual's ability to recognize, understand, and manage their own emotions and those of others. In the context of everyday life, EI plays a crucial role in dealing with various challenges and problems that arise. Individuals with high levels of emotional intelligence tend to demonstrate greater resilience when faced with failure. This ability not only contributes to personal development but also influences social interactions and interpersonal relationships. Several previous studies on the effect of EI on performance have shown conflicting results. Therefore, this study aims to re-examine the effect of EI on employee performance, but with the analysis focused on employees in the business sector in Makassar. By further exploring the importance of emotional intelligence in everyday contexts and its impact on individual performance, both in social and professional settings, it is hoped that this will provide broader insight into the importance of EI in supporting employee performance. The quantitative approach was conducted through simple regression analysis, first collecting data from 100 selected respondents working in the business sector. Prior to data collection, the research instrument was tested for validity and reliability, with the results showing that all indicators were valid and reliable. The analysis showed that emotional intelligence has a positive and significant effect on employee performance in the business sector. The better a person's emotional intelligence of employee, the better their work performance. The implication of this research is that companies are advised to develop training programs focused on developing employee emotional intelligence. This training can cover a variety of aspects, from an introduction to the concept of EI and emotional management techniques to communication and empathy skills. By providing this training, companies not only improve individual skills but also create a more collaborative and supportive work culture.